Pengaruh APE Montessori Manich Math terhadap Kemampuan Berhitung Kelompok A Di RA Brudu Sumobito Jombang - Putri Ismawati; Ike Wahyu Ningtias (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
The objective to be achieved in this study was to determine the effect of APE Montessori Manic Math on the numeracy ability of group A RA Al Khodijah Brudu Sumobito Jombang, The research method used in the purpose of this study in the Quantitative method with the type of research being Experimental Research, population and sample of 27 children, the research instrument in the form of a checklist in order determine to fint out the numeracy ability of group A in RA Al Khodijah through APE Montessori Manic Math and documentation in the formof photos of children during the learning process, while assessment instrument uses ratting scale which is used for raw data in the form of numbers and more flexible to measure the kegia process.tan in a learning with observation method then the collected data is calculated as the total value. Data analysis techniques used are non parametric statistical analysis techniques using t-test for small correlated samples. The value of Z = -4.324 and the Asymp value Sig (tailed) 0, and Sig (2-tailed) smaller than 0.01 then Ha is accepted, it means there is a very significant influence so concluded there is a very significant effect of APE Montessori Manic Math on the ability to count group A in RA Al Khodijah Brudu Sumobito Jombang.